A Comparative Study on the Difference of Vocational Education between China and Germany - Li, Jiajun (Transactions on Social Science, Education and Humanities Research, 2024)
In recent years, China has attached great importance to the development of vocational education, and China is eager to improve itself by learning from the world’s advanced vocational education system. China has been cooperating with Germany since the last century and has learned the German dual system. However, there is still a gap between the two until now in vocational education. By comparing the differences between the two countries in vocational education in top-level design, colleges, universities, and society, this paper finds out the differences between China and Germany in vocational education and hopes to find out the problems in the above three aspects as well as in other aspects on the road of development of vocational education in China from these differences and provide some relatively feasible solutions, to further advance the development of vocational education in China. We hope to explore the problems in these three aspects and others in the development of Chinese vocational education from these differences and provide some relatively feasible solutions to further promote the development of Chinese vocational education.